ANALISIS KEBIJAKAN PUBLIK PEMERINTAH DAERAH DALAM PENINGKATAN KINERJA SEKRETARIS DESA DI KABUPATEN GIANYAR - Subarwati, Ida Ayu Nyoman; Andreas Noak, Piers; Erviantono, Tedi (CITIZEN CHARTER, 2014)
ABSTRAK Secretary of the village is the village that privilege was taken directly into a Civil Servant by the government in accordance with Government Regulation No. 72 of 2005 and Government Regulation No. 45 of 2007. This led to the emergence of two types namely Village Secretary appointed as civil servants and employees country which is placed into the village secretary. Thus need to know about coaching and placement policy for the incumbent secretary of the village through this research. Where is the location of the selected research Gianyar. To use traditional theory of public policy analysis and the theory of rational bureaucracy in reviewing the policy defined by the Local Government Gianyar. This research uses descriptive qualitative research method is a method of research that followed the study procedures and generate descriptive data. In collecting the data were interviews, observation and documentation. By using non-probability sampling technique to determine the appropriate sample. This study also uses some of the techniques of data analysis are: data collection, data reduction, data display, verification. The results of this study is that there is a public policy that is made ??by the local government and RKPDesAPBDes, but not yet effective, efficient and adequacy, or not enough to solve the problem of coaching for the village secretary. Based on the theory of rational bureaucracy there are three ways that have not been met in the implementation of the bureaucratic system in the Gianyar regency, namely: (1) there’s no rule of selection officials; (2) The officials can not quit from office in accordance with personal desires; (3) there’s no a clear career path. Key words: Village Secretary, Civil Servant, Coaching, Public Policy